Education on Sentencing Women as Victims of Pornographic Content (Analysis of Case Decision No. 2661/Pid.Sus/2020/Pn Mdn) - Chairuni Nasution (Universitas Syiah Kuala, 2021)
One example of a case of Women as Victims of Pornographic Content occurred in the decision of the Medan District court with decision number 2661/Pid.Sus/2020/PN Mdn. Legal protection efforts against women as victims of pornography regulated in laws and regulations and The nature of this research is descriptive analysis, using normative types of research, while the methods used in this research are library research methods and the data collection techniques used are primary and secondary. The conduct of defendant Arisman Harefa als Arisman Harefa als Ama Endru has been validly and conclusively proven guilty of committing the Criminal Act